Analysis of the effectiveness of Kupang City restaurant tax implementation (Case study of KFC Kota Lama) - Floris, Dennis R. R.; Nino, Indawati J.; Sahetapy, Stella Y.; Batilmurik, Ridolof W. (Journal of Practical Management Studies, 2024)
The purpose of analyzing the effectiveness of the implementation of restaurant tax at KFC Kota Lama Kota Kupang is to find out whether the restaurant has implemented the tax effectively or not. This research method is descriptive with a quantitative approach. The analysis tool used in this study is the formula Effectiveness = Realization of Restaurant Tax Revenue Target Restaurant Tax Revenue X 100%. The results of the study based on the effectiveness formula show that the percentage of effectiveness level at KFC Kota Lama is fluctuating because the average percentage yield reaches 88%-100%. In January the effectiveness rate of restaurant tax was included in the effective category, while in February, March and May the effectiveness rate of restaurant tax was included in the category of quite effective. The occurrence of percentage results that fluctuate every month due to unbalanced target and realization results.